Mental Health of the Participants of the Third Age University Program: A Cross-Sectional Study - Cybulski, Mateusz; Cybulski, Łukasz; Cwalina, Urszula; Kowalczuk, Krystyna; Krajewska-Kułak, Elżbieta (Frontiers in Psychiatry, 2020)
Introduction Population aging is a progressive demographic phenomenon observed in all countries worldwide. The progressive global process of population aging poses many threats, especially in the context of the mental health of the elderly. Third Age Universities are an essential preventive measure shown to improve the quality of life and psychological wellbeing of the elderly. Objectives The aim of this study was to analyze the mental status of older persons attending Third Age Universities in Poland, with particular emphasis on sociodemographic sources of variance in psychological indices. Methods The study included a group of the Third Age University program participants from Poland. A total of 247 persons were enrolled, among them 215 women and 32 men. The study was carried out as a diagnostic survey, using the following validated psychometric scales: The Mood Disorder Questionnaire (MDQ), Geriatric Depression Scale (GDS), General Health Questionnaire-28 (GHQ-28), The Athens Insomnia Scale (AIS), Courtauld Emotional Control Scale (CECS), State-Trait Anxiety Inventory (STAI) and SMAST-G—Short Michigan Alcoholism Screening Test—Geriatric Version. Results The vast majority of the respondents did not screen positively for possible bipolar disorder. However, more than 90% of the participants presented with the symptoms of mild depression, and more than one-third had manifestations of non-psychotic mental morbidity. Nearly half of the respondents had complaints associated with insomnia, and in more than one-fourth, SMAST-G score raised suspicion of problem alcohol drinking. Retired participants were shown to present with significantly higher levels of anger control than the occupationally active respondents. Respondents with poor economic status had significantly higher levels of symptoms for non-psychotic mental disorders. Men significantly more often than women showed symptoms raising suspicion of alcohol-related problems. Discussion In conclusion, the study group was characterized primarily by the mild depressive and anxiety symptoms. The mental health of the Polish participants of the Third Age University program was significantly modulated by their socio-occupational and marital status, and financial condition. The study showed that persons with likely problem alcohol drinking differed from other respondents in terms of the occurrence of possible bipolar disorder, depression, and non-psychotic symptoms of mental disorders, state and trait anxiety levels and anger control. There is a need for further research in the field of mental health status in the Third Age Universities seniors to determine the prevalence of these phenomena on a national scale.